Pengaruh Sosialisasi Keuangan Terhadap Perilaku menabung Melalui Literasi Keuangan Dan Pengelolaan Pada Generasi Z Di Kota Tanjung Balai - Reiza Hasmaini; Siregar, Qahfi Romula (Balance : Jurnal Akuntansi dan Manajemen, 2024)
This research reviews the influence of financial socialization on saving behavior through financial literacy and financial management in Generation Z in Tanjung Balai City. The research aims to test, analyze and determine the influence of financial socialization on saving behavior through financial literacy and financial management in Generation Z in Tanjung Balai City. This research approach uses associative and quantitative research. And this research uses survey research by distributing a list of statements such as a questionnaire. The sample from this research was taken from one population, namely Generation Z in Tanjung Balai City, a sample of 100 respondents. In analyzing the data using Partial Least Square calculations with the SmartPLS application to be able to test the 7 hypotheses mentioned in this research. The research results show that financial socialization has a significant influence on saving behavior. Financial Socialization has a significant influence on Financial Literacy. Financial Socialization has a significant influence on Financial Management. Saving behavior has a significant influence on Financial Literacy. Saving behavior has a significant influence on Financial Management. And indirectly, financial socialization has a significant influence on saving behavior through financial literacy. Financial Socialization has a significant influence on saving behavior through Financial Literacy in Generation Z in the city of Tanjung Balai.